2018
DOI: 10.14569/ijacsa.2018.091187
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of an IoT-Based Flood Alert System

Abstract: Floods are the most damaging natural disaster in this world. On the occasion of heavy flood, it can destroy the community and killed many lives. The government would spend billions of dollars to recover the affected area. It is crucial to develop a flood control system as a mechanism to reduce the flood risk. Providing a quick feedback on the occurrence of the flood is necessary for alerting resident to take early action such as evacuate quickly to a safer and higher place. As a solution, this paper propose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 2 publications
(3 reference statements)
0
6
0
1
Order By: Relevance
“…Along these ideas, Shah et al [26] proposed a flood warning system built using Raspberry Pi. The Raspberry Pi is connected with several sensors such as an ultrasonic sensor, camera and rain gauge to determine the water level of the station every 10 microseconds and capture the condition of the station every 5 minutes.…”
Section: Long Range Communication (Lora)mentioning
confidence: 99%
“…Along these ideas, Shah et al [26] proposed a flood warning system built using Raspberry Pi. The Raspberry Pi is connected with several sensors such as an ultrasonic sensor, camera and rain gauge to determine the water level of the station every 10 microseconds and capture the condition of the station every 5 minutes.…”
Section: Long Range Communication (Lora)mentioning
confidence: 99%
“…A system to detect inundation stages by measuring the upsurge in water levels and alerting local residents was proposed by Shah et al [20]. The waterfall model as a methodology with Raspberry Pi was used to gather information from deployed sensors which transmitted it to the Global System for Mobile communication (GSM) module.…”
Section: The Implementation Of An Iot-based Flood Alert Systemmentioning
confidence: 99%
“…It is observed that EWIN might offer a superior approach, since it uses faster communication protocols and a centralized information system. In another similar work, “The Implementation of an IoT-Based Flood Alert System” [ 14 ], the alert processing is made at each node. The node processing power can be a handicap in comparison with the proposed system that uses a dedicated server for such task.…”
Section: Introductionmentioning
confidence: 99%